Embryonic Hadith Forgery at the Time of the Prophet - Fathur Rozi (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study discusses the phenomenon of hadith forgery that is thought to have occurred during the time of the Prophet Muhammad. Although there are differences of opinion among scholars regarding when this phenomenon first appeared, most arguments support that the forgery had its origins since the time of the Prophet, albeit on a limited scale. This study uses a descriptive qualitative approach with a library research method. Primary data sources are al-Mu'jam al-Awsat by al-Tabrani, Sarh Muskil al-Athar by al-Tahawi and Manhaj Naqd al-Matan Inda Ulama al-Hadith al-Nabawi by Salah al-Din al-Idlibi, as well as a number of other supporting literature. The analysis was conducted using the content analysis method to explore the motives and context of hadith forgery during the Prophet's time. The study found that attempts to falsify hadith during the Prophet's time had already existed as evidenced by several reports that indicated lies in the name of the Prophet and tended to be carried out by parties with worldly motives, not to fundamentally change religious teachings. This finding makes an important contribution in understanding the historical dynamics of hadith authenticity.Keyword: hadith forgery, the time of the prophet, historical study